DIGITALISASI DAN PELUANG EDUPRENEURSHIP BAGI INDUSTRI BATIK PEKALONGAN - Ziyadah El Fadllilah; Rizqi Nur Amalya; Brillian Galang Irzaqi; Hikmah Ramadhani; Aulia Damayanti; Ferida Rahmawati (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
Batik, as one of Indonesia’s cultural heritages, continues to evolve and is no longer regarded solely as a traditional craft, but has become an important part of today’s creative industry. This study aims to describe how batik is produced, the philosophical meanings embedded in its motifs, and the business opportunities that emerge as digital technology becomes increasingly integrated into production and marketing practices. Using a descriptive qualitative approach, this research illustrates how traditional batik-making processes are now combined with various forms of digital innovation, such as social-media-based promotion and the use of online marketplace platforms to reach a wider audience. The findings show that digitalization does not only help artisans expand their market reach but also improves promotional effectiveness and strengthens brand identity. In addition, this study supports previous research indicating that digital technology plays a crucial role in maintaining the sustainability of batik businesses amid growing global competition.